Explicit inflation objectives and macroeconomic outcomes - Andrew T. Levin; Fabio M. Natalucci; Jeremy M. Piger (European Central Bank (ECB), 2004)
We find evidence that adopting an explicit inflation objective plays a role in anchoring long-run inflation expectations and in reducing the intrinsic persistence of inflation. For the period 1994-2003, private-sector long-run inflation forecasts exhibit significant correlation with lagged inflation for a number of industrial economies, including the United States. In contrast, this correlation is largely absent for the five countries that maintained explicit inflation objectives over this period, indicating that these central banks have been reasonably successful in delinking expectations from realized inflation. We also show that the null hypothesis of a random walk in core CPI inflation can be clearly rejected for four of these five countries, but not for most of the other industrial countries. Finally, we provide some evidence concerning the initial effects of the adoption of explicit inflation objectives in a number of emerging-market economies.
Keywords: E31; E52; E58; 330; Consensus Forecasts; inflation expectations; inflation persistence